MicroRNA-92a-3p Enhances Cisplatin Resistance by Regulating Krüppel-Like Factor 4-Mediated Cell Apoptosis and Epithelial-to-Mesenchymal Transition in Cervical Cancer - Jing Yang; Jing Hai; Xuecai Dong; Mengjie Zhang; Shufeng Duan (Frontiers Media S.A., 2022)
Recent studies have confirmed the existence and key roles of microRNA (miRNAs) in cancer drug resistance, including cervical cancer (CC). The present study aims to establish a novel role for miR-92a-3p and its associated gene networks in cisplatin (DDP) resistance of CC. First, the disparities in miRNA expression between CC tissues and adjacent normal tissues were screened based on GSE19611 microarray data that retrieved from Gene Expression Omnibus (GEO), and we identified several miRs that were significantly downregulated or upregulated in CC tissues including miR-92a-3p. Moreover, miR-92a-3p was significantly up-regulated in DDP-resistant cells and was the most differently expressed miRNA. Functionally, knockdown of miR-92a-3p increased the sensitivity of DDP-resistant cells to DDP via inhibiting cell proliferation, migration and invasion, and promoting apoptosis. Conversely, overexpression of miR-92a-3p significantly induced DDP resistance in CC parental cells including HeLa and SiHa cells. Moreover, Krüppel-like factor 4 (KLF4) was identified as a direct target of miR-92a-3p, and an obvious inverse correlation was observed between the expression of miR-92a-3p and KLF4 in 40 pairs of cancer tissues. Furthermore, KLF4 knockdown reversed the promoting effect of miR-92a-3p inhibition on DDP sensitivity in DDP-resistant CC cells. Besides, high expression of miR-92a-3p was associated with DDP resistance, as well as a short overall survival in clinic. Taken together, these findings provide important evidence that miR-92a-3p targets KLF4 and is significant in DDP resistance in CC, indicating that miR-92a-3p may be an attractive target to increase DDP sensitivity in clinical CC treatment.